Sustained effort : the life of Sir Leonard Isitt : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Defence Studies at Massey University, Palmerston North, New Zealand - Sutcliffe, Devon (Massey University, 2011)
This thesis examines the life of Sir Leonard Isitt, and his contribution to New Zealand aviation, first from a service perspective, and then considers his involvement with commercial aviation. Isitt commenced his military career as a foot soldier, serving first in Egypt during 1915, and then on the Somme, where he was seriously wounded in September 1916. While convalescing he arranged a transfer to the Royal Flying Corps, where he trained as a pilot, before undertaking two tours of duty on the Western Front. After the War Isitt remained in the United Kingdom undertaking various courses, before returning in late 1919 to join the embryo New Zealand Air Force. He became the first Commanding Officer at Wigram, and then took command of the operational station at Hobsonville. When the Royal New Zealand Air Force was created in 1937, he became the first Air Member for Personnel on the Air Board, and oversaw the build-up of personnel in anticipation of the Second World War. With the declaration of war, Isitt was posted to Canada to monitor New Zealand’s contribution to the Empire Air Training Scheme, and was subsequently posted to Washington and London before returning to New Zealand as Deputy Chief of the Air Staff in early 1943. In mid-1943 he was appointed Chief of the Air Staff, the first New Zealander to hold this position, and saw the RNZAF build its strength to 20 active squadrons, equipped with over 1300 aircraft and supported by 45,000 staff. At the end of the War, Isitt was chosen to sign the Japanese Surrender Document on behalf of New Zealand at a ceremony on USS Missouri in Tokyo Bay. Isitt was knighted in 1946 and retired from the RNZAF to become Chairman of Directors of the nationalised airline New Zealand National Airways Corporation. He also became Chairman of Tasman Empire Airways Ltd and served as New Zealand nominee on the Board of British Commonwealth Airways Ltd. Isitt finally retired in 1963, after spending over forty years in the forefront of New Zealand aviation, and during this period arguably had a greater influence in this sector than any other person.
Keywords: Leonard Isitt, Sir; New Zealand aviation; Chief of air staff biography; Military career; New Zealand Air Force; World War One; World War Two; First World War; Second World War; New Zealand National Airways Corporation; NAC; Tasman Empire Airways; National Airways Corporation; World War I; World War II